Effect Of Use Of The Focusky Application On Results Learning Arts And Culture For Class X Students Madrasah Aliyah Ddi Kulo - Aini, Aini; M, Usman; B, Hasanuddin; Hermansyah, Sam (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. Researchers will examine the impact of the Focusky app on Arts and Culture learning for 10th-grade students at Madrasah Aliyah DDI Kulo. Pre-observation reveals conventional teaching methods in use. The introduction of Focusky is expected to enhance learning, offering a dynamic experience for both students and teachers.Top of Form. Purpose.This study on the use of the Focusky application in Arts and Culture education for 10th-grade students at Madrasah Aliyah DDI Kulo is expected to contribute significantly. Findings may enhance teaching methods, particularly in the Arts, improving overall learning quality and simplifying the educational process. Method.This use method approach quantitative. According to Sugiyono (2017) study quantitative is